Bioavailability enhancement of baclofen by gastroretentive floating formulation: statistical optimization, in vitro and in vivo pharmacokinetic studies. (June 2013) - Thakar, Krishna; Joshi, Garima; Sawant, Krutika K.
<x xml:space="preserve">Abstract</x> Objectives: The study was aimed to improve bioavailability of baclofen by developing gastroretentive floating drug delivery system (GFDDS). Methods: Preliminary optimization was done to select various release retardants to obtain minimum floating lag time, maximum floating duration and sustained release. Optimization by 32 factorial design was done using Polyox WSR 303 (X1) and HPMC K4M (X2) as independent variables and cumulative percentage drug released at 6 h (Q6h) as dependent variable. Results: Optimized formulation showed floating lag time of 4–5 s, floated for more than 12 h and released the drug in sustained manner. In vitro release followed zero ordered kinetics and when fitted to Korsemeyer Peppas model, indicated drug release by combination of diffusion as well as chain relaxation. In vivo floatability study confirmed floatation for more than 6 h. In vivo pharmacokinetic studies in rabbits showed Cmax of 189.96 ± 13.04 ng/mL and Tmax of 4 ± 0.35 h for GFDDS. The difference for AUC(0–T) and AUC(0–∞) between the test and reference formulation was statistically significant (p > 0.05). AUC(0–T) and AUC(0–∞) for GFDDS was 2.34 and 2.43 times greater than the marketed formulation respectively. Conclusion: GFDDS provided prolonged gastric residence and showed significant increase in bi oavailability of baclofen.